Influence of co-solvent on reactive-extraction of Jatropha curcas L. seed for biodiesel production - M. Dani Supardan; . Satriana; Ryan Moulana (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
In this study, experimental studies have been carried out to improve the yield of biodiesel by addition of co-solvent to enhance the miscibility of the phases and speed up the reaction rate. The co-solvent used are tetrahydrofuran and hexane. The experimental result shows that the transesterification rate was improved when compared to the system without cosolvents. The biodiesel produced in the experiment was analyzed by gas chromatography-mass spectrometry (GC-MS), which showed that methyl oleate was the highest compound in biodiesel.